Effects of Dietary Inclusion of Angelica gigas Nakai root extract on the Growth Performance, Hematological and Serum Biochemical Parameters in Broilers - dela Cruz, Joseph Flores; Purnamasari, listya; Hwang, Seong Gu (Buletin Peternakan, 2024)
The study aimed to evaluate the impact of dietary supplementation with Angelica gigas Nakai (AGN) root extract on growth performance, hematological indices, and serum biochemical parameters in broiler chickens. A total of 320 straight-run Cobb broiler chicks from a commercial hatchery were distributed among four treatment groups: Basal diet (BD) as the Control; Treatment 1 (T1): BD + 2 g/kg AGN; Treatment 2 (T2): BD + 4 g/kg AGN; and Treatment 3 (T3): BD + 8 g/kg AGN), each comprising eight replicates with 10 birds per replicate. The supplementation of AGN resulted in dose-dependent improvements (P < 0.05) in body weight, gain, and feed efficiency. On both day 21 and day 35, increasing AGN dosage in the diet led to a significantly higher (P < 0.05) values of red blood cells (RBCs), white blood cells (WBCs), hemoglobin (Hb), and packed cell volume (PCV). By day 21, AGN supplementation dose-dependently decreased (P < 0.05) serum alkaline phosphatase (ALP), aspartate aminotransaminase (AST), alanine aminotransaminase (ALT), urea, and creatinine levels. Meanwhile, AGN dose escalation correlated with a notable increase (P < 0.05) in serum total protein (TP), albumin, and globulin levels. On day 35, increasing AGN levels led to a significant reduction (P < 0.05) in serum AST and ALT activity, along with lowered serum glucose, cholesterol, triglycerides, urea, and creatinine levels. In conclusion, AGN supplementation enhanced growth performance and positively influenced hematological indices and serum biochemistry profiles in broiler chickens. The study confirms the safe and effective utilization of AGN at an 8 g/kg (0.8 %) feed additive dosage to optimize broiler performance. These findings provide valuable insights into the potential benefits of AGN in poultry nutrition.